Bridging the gap: ethical considerations of providing psychological assessment results in research studies. Issue 6 (18th August 2021) - Kirsch, Alexandra C.; Zaccariello, Michael J.; McCormick, Jennifer B.; Sharp, Richard R.; Flick, Randall P.; Warner, David O.
ABSTRACT: There is limited guidance about whether and how to provide psychological assessment results to research participants. This paper considers several ethical challenges associated with offering individual research results in psychological assessment research. Additionally, the process used to return individual results within a study examining neurodevelopmental effects of anesthesia exposure in children and adolescents is described. Almost all participants requested to know if results were concerning; however, only around a third of those with concerning findings sought additional feedback. Ongoing research and guidance are necessary to establish evidence-based practices and manage challenges that may emerge when disclosing such results.